Reliable and Energy Efficient Streaming Multiprocessor Systems - Das, Anup Kumar; Kumar, Akash; Veeravalli, Bharadwaj; Catthoor, Francky (Embedded Systems, 2018)
This book discusses analysis, design and optimization techniques for streaming multiprocessor systems, while satisfying a given area, performance, and energy budget. The authors describe design flows for both application-specific and general purpose streaming systems.  Coverage also includes the use of machine learning for thermal optimization at run-time, when an application is being executed.  The design flow described in this book extends to thermal and energy optimization with multiple applications running sequentially and concurrently.